Storynomics Bali Aga: Pemanfaatan Cerita Rakyat untuk Promosi Desa Wisata Sidetapa, Kabupaten Buleleng - Laksmita Sari, Ida Ayu; Putra, I Nyoman Darma; Purnawan, Ni Luh Ramaswati; Suardiana, I Wayan (Jurnal Master Pariwisata (JUMPA), 2022)
Stories about tourist attractions can add dimensions to the quality of the attraction and the tourist experience. This article analyzes the benefits of folklore in improving the quality of tourist attractions in Sidetapa Tourism Village, Banjar District, Buleleng Regency. The village, which is classified as an ancient Balinese village, has begun to develop itself as a tourist village and has a tourist attraction related to the village’s folklore. This qualitative research begins with identifying folklore and selecting those related to tourist attractions in Sidetapa Village. By using the storynomics approach, the selected stories are then arranged in two forms, namely the complete form and the concise form. This story is prepared for tourism-awareness groups that can be used as material in guiding tours. This article contributes to showing the reciprocal benefits of folklore and tourist attraction, in terms of the role of folklore to increase the dimensions of the quality of tourist attraction and the benefits of tourism activities in preserving folklore by introducing them to the public and tourists. Keywords: folklore, storynomics, Sidetapa Tourism Village, tourist attraction, tourist experience